2022
DOI: 10.1212/wnl.0000000000200018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acute Alteration of Consciousness in Patients With Acute Ischemic Stroke With Outcomes and Early Withdrawal of Care

Abstract: Background and ObjectivesEarly consciousness disorder (ECD) after acute ischemic stroke (AIS) is understudied. ECD may influence outcomes and the decision to withhold or withdraw life-sustaining treatment.MethodsWe studied patients with AIS from 2010 to 2019 across 122 hospitals participating in the Florida Stroke Registry. We studied the effect of ECD on in-hospital mortality, withholding or withdrawal of life-sustaining treatment (WLST), ambulation status on discharge, hospital length of stay, and discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Unfortunately, in the NCCU, WLST is often driven by factors that are either nonmedical or temporary. 2,6,7 This occurs despite the fact that multiple studies, including the current article, have shown that most patients with severe TBI have favorable outcomes. 8 We feel that this manuscript adds meaningfully to the growing body of evidence that the science of early prognostication in the NCCU is lacking for even our most common diseases and thus WLST should rarely be entertained in the intensive care unit.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Unfortunately, in the NCCU, WLST is often driven by factors that are either nonmedical or temporary. 2,6,7 This occurs despite the fact that multiple studies, including the current article, have shown that most patients with severe TBI have favorable outcomes. 8 We feel that this manuscript adds meaningfully to the growing body of evidence that the science of early prognostication in the NCCU is lacking for even our most common diseases and thus WLST should rarely be entertained in the intensive care unit.…”
mentioning
confidence: 79%
“…Unfortunately, in the NCCU, WLST is often driven by factors that are either nonmedical or temporary. 2,6,7 This occurs despite the fact that multiple studies, including the current article, have shown that most patients with severe TBI have favorable outcomes. 8…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We found higher rates of WLST in hemorrhagic strokes when compared to ischemic stroke; consistent with prior literature. These higher rates might in part be related to impaired level of consciousness, cerebral edema, and herniation syndromes that are seen more commonly after hemorrhagic strokes (9–11). The rates of WLST were stable overtime in comparison to the mortality rates (in decline), highlighting the limitation of the current prognostication practices.…”
Section: Discussionmentioning
confidence: 99%
“…WLST is more commonly seen after ICH and SAH than AIS (9)(10)(11). Factors such as age, stroke severity, and impaired level of consciousness may influence WLST decisions (10)(11)(12)(13). The temporal trends and predictors of WLST decision during hospitalization are not well studied.…”
mentioning
confidence: 99%